2013
DOI: 10.1093/scan/nst165
|View full text |Cite
|
Sign up to set email alerts
|

The world can look better: enhancing beauty experience with brain stimulation

Abstract: Aesthetic appreciation is part of our everyday life: it is a subjective judgment we make when looking at a painting, a landscape, or--in fact--at another person. Neuroimaging and electrophysiological evidence suggests that the left dorsolateral prefrontal cortex (DLPFC) plays a critical role in aesthetic judgments. Here, we show that the experience of beauty can be artificially enhanced with brain stimulation. Specifically, we show that aesthetic appreciation of representational paintings and photographs can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
47
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 43 publications
(56 reference statements)
9
47
5
Order By: Relevance
“…This can be done by examining how changes in neural activity in local areas modulate aesthetic experiences. For example, applying anodal (excitatory) transcranial direct current stimulation to the left dorsolateral prefrontal cortex made individuals like representational paintings and photographs more than they did under sham stimulation conditions . Extending earlier MEG findings, these new results show that activating a region correlated with aesthetic judgments (i.e., the left dorsolateral prefrontal cortex) can influence aesthetic experience.…”
Section: Art Productionsupporting
confidence: 71%
“…This can be done by examining how changes in neural activity in local areas modulate aesthetic experiences. For example, applying anodal (excitatory) transcranial direct current stimulation to the left dorsolateral prefrontal cortex made individuals like representational paintings and photographs more than they did under sham stimulation conditions . Extending earlier MEG findings, these new results show that activating a region correlated with aesthetic judgments (i.e., the left dorsolateral prefrontal cortex) can influence aesthetic experience.…”
Section: Art Productionsupporting
confidence: 71%
“…The former are generally considered as visual areas although the precuneus has also been related to social processes (14) and is related to the fantasy content of visual materials (15). Activation of the mFPC is consistent with findings that the mPFC figures prominently in explanations of processes that have an affective component; furthermore, the medial orbitofrontal cortex and the ventromedial prefrontal cortex are activated when people judge objects to be beautiful (5, 1619). Interestingly, the main activation in this contrast can be related to thepleasure/reward/appetitive component in the model by Chatterjee (10).…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, one might perceive certain facial structures that remind one of a loved person as particularly beautiful, thus leading to a slightly biased evaluation of shown image material. It has, for example, been shown that transcranial current stimulation of the left dorsolateral prefrontal cortex enhances aesthetic appreciation, 17 which points out that perception of beauty can clearly be altered by different mechanisms. Thus, it seems that beauty does not only lie in the eyes but also in the brain of the beholder.…”
Section: Discussionmentioning
confidence: 99%